Tackling Online Terrorist Content Together: Cooperation between Counterterrorism Law Enforcement and Technology Companies - Stuart Macdonald (Global Network on Extremism and Technology, 2023)
Cooperation between law enforcement and tech companies is widely regarded as necessary to tackle online terrorist content. Both sectors have publicly stated their commitment to working together, and there have been examples of mutual cooperation. Yet there are also impediments to such collaboration, including different cultures and operating practices, and there have been high-profile instances of non-cooperation. The informality of existing collaborations has also led to concerns about censorship, mission creep and a lack of accountability and oversight.The focus of this report is how to resolve the impediments to closer law enforcement – tech sector cooperation, in order to realise the benefits of mutual collaboration, while simultaneously addressing concerns about due process and accountability. The report utilises an interview-based methodology to examine the experiences and opinions of personnel from both sectors with first-hand experience of mutual cooperation, and provide an empirically grounded insight to this under-researched topic. It concludes with four recommendations: the development of an experience exchange programme; the implementation of a takedown‑shutdown counterterrorism policing protocol; a joint upstreaming programme founded on a proactive preventative ethos; and the development of joint strategic research requirements.